Upaya Pencegahan Korupsi Melalui Nilai Anti-Korupsi pada Generasi Muda - Handy Setiawan (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
Corruption is a global issue that significantly impacts social, economic, and political aspects, particularly in developing countries like Indonesia. It undermines public trust in government institutions and contributes to social injustice, slowing economic growth and hindering overall welfare. This paper focuses on preventing corruption among the younger generation, highlighting key measures such as anti-corruption education in schools, the effective use of social media campaigns, and necessary reforms in law enforcement. By instilling values of integrity and responsibility early on, educational institutions can help shape future leaders who are prepared to combat corruption. Additionally, the effective use of social media platforms like Instagram, TikTok, and YouTube can engage the younger generation through creative and interactive content, fostering awareness and encouraging active participation in anti-corruption efforts. Reforming law enforcement to impose stricter penalties on corrupt individuals and providing protection for whistleblowers are crucial to creating a deterrent effect. Ultimately, a comprehensive approach involving education, technology, and legal reform can empower the younger generation to promote transparency and integrity, contributing to a corruption-free society and a stronger foundation for the nation’s future